In Defense of a Just Society: Buber Contra Gandhi on Jewish Migration to Palestine - Skiles, William Stewart (Religions, 2023)
Much has been written on Martin Buber’s public response to Mahatma Gandhi’s article “The Jews”, which had been published in the newspaper Harijan in 1938, just after the Nazi pogrom against the Jews known as “Kristallnacht”. I wish to examine more closely Buber’s conception of God’s command to the Jewish people to settle the land of Palestine in a manner that expresses love for their Arab neighbors, seeks harmony and peace in the land, and serves not only the common good among Jews and Arabs but the good of the land itself—that it would be fruitful for all. Central to Buber’s conception of the state of Israel in Palestine—and Jewish settlement more generally—was God’s ancient command that the Jews must establish a just society. The Jews must be faithful, Buber contended, to build a community and state that obeys God’s calling and aligns with their mission to reflect God’s justice in the world. Thus, understanding and harmony between the Jews and Arabs must be integral to the Jews’ approach to Arabs in Palestine, not peripheral to their mission. Buber’s response demonstrates his desire to relate directly and personally to Gandhi, to reveal falsehoods and misunderstandings, and to facilitate a greater awareness of the richness of the Jewish tradition that may be used to benefit the land of Palestine and its peoples. This vision for the Jewish mission deserves more attention in the historiography.